GROUNDWATER CHEMICAL STUDIES USING STATISTICAL ANALYSIS IN COIMBATORE CORPORATION, TAMIL NADU, INDIA - Shantharam, Y.; Elangovan, K. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In place with comprehend the hydrochemistry and the probable contamination of groundwater for drinking and irrigation purposes, 60 groundwater samples have been collected from Coimbatore Corporation region in march 2014 and various physicochemical parameters (pH, EC, TDS, Alkalinity, TH, Ca2+, Mg2+, Na+, K+, Fe2+, NH3, NO2-, NO3-, Cl-, F-, SO42- and PO42-) were analysed. The concentrations of physiochemical parameters in the studied samples were compared with the WHO standards to study the suitability of water for drinking purpose. The statistical analysisÂ â€œQ-mode factorâ€ and â€œcluster analysesâ€ were carried out and found that geology and exchange between the river water and the groundwater plays a dominant role in the hydro chemical evolution of groundwater. Cluster tree diagram reveals that 41.67% of the study area comes under cluster I, II and III classification. Cluster tree clearly reveals that elevation high automatically geochemical concentration is low. The geochemical concentration is inversely proposed to elevation. A long term management strategy should be formulated for the protection of groundwater resources for drinking and agricultural activities.